Understanding the use of health supplements in patients with chronic diseases: findings and implications. - Khan, Fareed; Anwar, Muhammad; Ishaq, Rabia; Iqbal, Qaiser; Haider, Sajjad; Raziq, Abdul; Tareen, Abdul Malik; Mengal, Mohammad Alam; Jan, Syed Umer; Saleem, Fahad (Journal of Public Health: From Theory to Practice (2198-1833), 2023)
Background: Although the use of health supplements is frequently reported, patients' understanding of health supplement use and related safety concerns are least reported from the developing world. Aim: This study was aimed to assess the understanding of health supplement use in patients with chronic diseases visiting a public healthcare institute of Quetta city, Pakistan. Methods: A cross-sectional study with a proportioned based sample of 460 patients with chronic diseases attending a tertiary care hospital of Quetta city was carried out. A pre-validated questionnaire was used to assess patients' understanding of health supplement use. SPSS version 21.0 was used for data analysis. Both descriptive and inferential statistics were used. For all analyses, p < 0.05 was taken as significant. Results: Most of the patients were more than 47 years of age, with a mean age of 51.62 ± 12.71 years. Thirty-three percent of the patients were diagnosed with hypertension, followed by 17.1% with hypertension + diabetes mellitus Type II. Friends and relatives (195, 42.3%) were the most common source of information regarding health supplements, and multivitamins & minerals (n = 268) were the most used health supplements. Almost 80% of the respondents have neither discussed nor disclosed the use of health supplements with their doctors or pharmacists. Nearly the same percentage (80%) of the respondents were unaware of the safety concerns of health supplements, nor were they aware of either interactions or side–effects. Education and disease state were significantly associated with certain items of the questionnaire. Bonferroni correction revealed graduates and patients with hypertension + diabetes mellitus Type II agreeing to the mentioned statements. Conclusion: Inadequate understanding of health supplements was reported by the study respondents. As health supplement use is linked with certain safety concerns, enhancing patients' understanding about misconceptions with regard to the safety and efficacy of supplements and their appropriateness is needed and must be addressed as a priority.